Pembuatan Sistem Informasi Pengelolaan Data Penjualan dan Stok Distributor Sandal di CV. MAKMUR - Djulwini Fred Dachi; Hevalda Eppa; Muthmainnah Muthmainnah; Johni S. Pasaribu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
As a distributor company CV. MAKMUR needs to use information technology not only for selling its products but also in warehouse inventory management, where there is no longer recording and calculating inventory using Microsoft Excel, where there are several errors such as errors in recording goods and taking long reporting processes. The collection of data obtained are interviews, observations and literature studies, while software development uses the classical waterfall methodology which consists of stages: needs analysis, design, implementation and testing. For system design through an object-oriented approach with the Unified Modeling Language (UML) tool. Through this application, it is hoped that the service process to consumers can be clear and fast. In addition, this inventory application can be used as inventory material for products that are in stock used in the warehouse which includes recording, processing, and reporting data on warehouse inventory. Keywords : Information System, Management, Sales, Stock